Administrasi pengelolaan sekolah dan madrasah database berbasis digital - Muchofifah, Azza Rukyatul (Maliki Interdisciplinary Journal, 2024)
The administration of schools and madrasahs through digital databases is an educational innovation aimed at improving efficiency, transparency, and data accuracy. This study seeks to understand the implementation and impact of digital systems such as Dapodik (Education Data Center) and EMIS (Education Management Information System) in educational management. A qualitative approach was employed, involving in-depth interviews and observations with school principals, teachers, and system operators. The results show that digital systems facilitate data management, enhance reporting efficiency, and reduce administrative burdens. However, challenges remain, including infrastructure limitations and gaps in staff skills. This study recommends providing more training and technological facilities to optimize the implementation of these systems.